THE CONTROL SYSTEM IMPROVEMENT OF HEATING BOOKS FOR A PASSENGER CAR - Prykhodko, V. I.; Shkabrov, O. A.; Ihnatov, H. S.; Vysokolian, M. V.; Makarenko, V. M.; Myrhorodska, A. I. (Science and Transport Progress, 2005)
In article the description of the advanced monitoring system of heating of axle boxes of the new carriage with an opportunity of registration of necessary parameters is offered.